Predicting of Factors influencing physical activity in women for the prevention of osteoporosis according the Precede Model - Nasrin Tabasinejad; Seyed Vahid Ahmadi Tabatabaei; Narges Khanjani; Mohabbat Mohseni (Kerman University of Medical Sciences, 2015)
Introduction: Osteoporosis is the most common metabolic bone disease which is nowadays known as a public health problem. Physical activity to maintain healthy bones is an important factor in preventing osteoporosis. The aim of this study was to determine a model for predicting factors influencing physical activity among women for the prevention of osteoporosis according to the Precede Model in Kerman, Iran. Method: This cross-sectional analytical descriptive study was performed on 120 women referred to health centers of Kerman city during 2014. They were selected randomly through multi- stages sampling method. Data were collected using the International Physical Activity Questionnaire (IPAQ) and a self-administrated questionnaire according to constructs of the PRECEDE Model (Predisposing Reinforcing, and Enabling Factors) andanalyzed by descriptive statistics (measures of central tendency, dispersion, frequency and percent) and analysis statistics (logistic regression, Pearson correlation) using SPSS software version 18. Results: The results showed thatthe mean age of the participants were 32.44 ± 6.97 years. 29.2% of women had intense, 5.35% moderate, and 7.66% mild physical activity. The results also indicated that enabling factors was the most predictive factors of physical activity both in raw (P=0.023, OR=1/122) and adjusted models (P=0.041, OR=1/137). Conclusion: As enabling factors were the most important predictive factor for physical activity, it is recommended that health promotion interventions be planned according to these factors to improve physical activity and prevent osteoporosis mong women. Keywords: Predicting, Physical Activity, Osteoporosis, Women, Precede Model Citation: Tabasinejad N, Ahmadi Tabatabaei SV, Khanjani N, Mohseni M. Predicting Factors Influencing Physical Activity in Women for thePrevention of Osteoporosis According to the Precede Model. Journal of Health Based Research 2015 1(2): 155-166.